1993
DOI: 10.1084/jem.178.5.1473
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 (IL-10) upregulates functional high affinity IL-2 receptors on normal and leukemic B lymphocytes.

Abstract: SummaryInterleukin 10 (IL-10) has recently been shown to induce normal human B lymphocytes to proliferate and differentiate into immunoglobulin (Ig)-secreting cells. Herein, we show that IL-10 also promotes DNA synthesis and IgM production by anti-CD40 activated B cell chronic lymphocytic leukemia (B-CLL). Most strikingly, IL-2 and IL-10 were found to synergize to induce the proliferation and differentiation of B-CLL cells. This synergy between IL-2 and IL-10 was also observed with normal B cells which prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 40 publications
1
78
1
Order By: Relevance
“…6). The synergistic effect of IL-2 and IL-10 on growth and differentiation of human B cells has previously been attributed to the ability of IL-10 to increase expression of CD25 on CD40-activated B cells (29). Taken with our results, the B cells observed in this previous study to up-regulate CD25 were presumably memory B cells present in the population of total tonsillar B cells used (29).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…6). The synergistic effect of IL-2 and IL-10 on growth and differentiation of human B cells has previously been attributed to the ability of IL-10 to increase expression of CD25 on CD40-activated B cells (29). Taken with our results, the B cells observed in this previous study to up-regulate CD25 were presumably memory B cells present in the population of total tonsillar B cells used (29).…”
Section: Discussionsupporting
confidence: 79%
“…The synergistic effect of IL-2 and IL-10 on growth and differentiation of human B cells has previously been attributed to the ability of IL-10 to increase expression of CD25 on CD40-activated B cells (29). Taken with our results, the B cells observed in this previous study to up-regulate CD25 were presumably memory B cells present in the population of total tonsillar B cells used (29). Our results predict that differentiation of naive B cells into memory B cells in vivo will alter the proliferative behavior of the resulting memory B cells in terms of time to enter division, magnitude of the response, and the growth factors capable of affecting this response.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important biological implications, as the same stimuli that actively induce CSR, such as CD40L and IL-4, may enhance the in vivo accumulation of some elements of the CLL clone (52,54,56). Furthermore, ongoing CSR might introduce genomic instability.…”
Section: Cd40lmentioning
confidence: 97%
“…Importantly, T cells in the microenvironment may induce CD25 upregulation in B-CLL cells by providing CD40 ligand and IL-10 as well as IL-2 [14,32]. IL-2 is then able to both induce proliferation and prevent apoptosis in the malignant cells and might 12 therefore play a central role in the balance between proliferation and apoptosis, which is determined in lymphoid tissues [40].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that upregulation of CD25 in stimulated B-CLL cells results in the formation of functional high affinity receptors [13,14]. Importantly, IL-2 has demonstrated its potency to increase Immunglobulin secretion, cytokine production and upregulation of surface 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62...…”
mentioning
confidence: 99%